2016
DOI: 10.3928/01477447-20151222-02
|View full text |Cite
|
Sign up to set email alerts
|

Knee Osteoarthritis: Does Transcutaneous Electrical Nerve Stimulation Work?

Abstract: Transcutaneous electrical nerve stimulation has been proposed as a nonoperative treatment for osteoarthritis. The purpose of this study was to evaluate the outcomes of a novel transcutaneous electrical nerve stimulation device compared with those of other standard nonoperative modalities for the treatment of osteoarthritis of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
(29 reference statements)
2
7
0
1
Order By: Relevance
“…These results concur with a previous study in which performed a three-week TENS intervention on patients with knee osteoarthritis [19]. This is in line with a previous study in which 36 patients with knee osteoarthritis were treated with TENS intervention for six weeks and significant pain reduction after intervention [20]. This result is because TENS selectively increases the input of the large fibers, thereby reducing the presynaptic inhibition of paintransmitting cells (T-cells) and reducing the perception of conscious pain [21].…”
Section: ⅳ Discussionsupporting
confidence: 93%
“…These results concur with a previous study in which performed a three-week TENS intervention on patients with knee osteoarthritis [19]. This is in line with a previous study in which 36 patients with knee osteoarthritis were treated with TENS intervention for six weeks and significant pain reduction after intervention [20]. This result is because TENS selectively increases the input of the large fibers, thereby reducing the presynaptic inhibition of paintransmitting cells (T-cells) and reducing the perception of conscious pain [21].…”
Section: ⅳ Discussionsupporting
confidence: 93%
“…The results of the current study are also come in consistence with the study of Cherian J.J et al, that concluded that about 70% of the patients experienced pain reduction when treated with low-TENS [30].…”
Section: Discussionsupporting
confidence: 68%
“…It is important to emphasize that variations in intensity and treatment duration could have compromised these studies. Even though stimulation intensity and maintenance are key factors for the success of the treatment, 37 it was not described in most studies, and it was only periodically adjusted to maintain sensory threshold by two studies. 11,15 This lack of standard may lead to analgesic tolerance 33 and to greater pain relief when given at the strongest possible intensity.…”
Section: Summary Of Evidencementioning
confidence: 99%